# Holder Inequality in Measure Theory

Jia-Ming Liou (Frank)
Department of Mathematics, University of California, Davis. E-mail: frankliou@math.ucdavis.edu Website: http://www.math.ucdavis.edu/∼frankliou/

January 21, 2008

1

Inequalities

Theorem 1.1. Let 1 < p < ∞ and f ∈ Lp , g ∈ Lq , where 1/p + 1/q = 1. Then f g ∈ L1 and f gdµ ≤ f
X p

g

q

.

Proof. If f

p

or g

q

equals to 0, then f or g are zero almost everywhere. Then f gdµ = 0.
X

In this case, the Holder inequality holds. We may assume that both f Let |f (x)| |g(x)| F (x) = , G(x) = , f p g q then F, G ≥ 0 and F (x)G(x) ≤ It is easy to see that F
p

p

or g

q

are not zero.

1 1 F (x)p + G(x)q . p q

= G

q

= 1, then 1 p F (x)p dµ +
X

F Gdµ ≤
X

1 q

G(x)q dµ = 1.
X

This implies that |f g|dµ ≤ f
X p

g

q

.

Since f gdµ ≤
X X

|f g|dµ,

then we proves the Holder inequality. Theorem 1.2. Assume that 1 < pk < ∞, for k = 1, ..., n, and f1 f2 ...fn dµ ≤ f1
X p1 n k=1

pk = 1. Then
pn

f2

p2

... fn

.

Proof. Without loss of generality, we may assume fk

pk

= 0 for all 1 ≤ k ≤ n. Deﬁne
pk

Fk (x) = |fk (x)| / fk where 1 ≤ k ≤ n, then
n

,

F1 (x)F2 (x)...Fn (x) ≤
k=1

F (x)pk . pk

1

We ﬁnd 1 1 F (x)p + G(x)q = F (x)G(x). This proves our assertion. p q 1 1 F (x)p + G(x)q − F (x)G(x). Using this.e.4...fn |dµ ≤ f1 X p1 f2 p2 .. Suppose that for each g ∈ Lq with g f gdµ ≤ f X p q p f g p p q q |g(x)| . G ≥ 0. we can prove the inequality.3.. Then deﬁne g(x) = sgn f |f (x)| p−1 / f −p p p−1 p . then n F1 .Since Fk pk = 1. q = 1. Prove that we can ﬁnd c ∈ R so that f (x)p = cg(x)q µ-a. For a given f ∈ Lp . we have F (x)G(x) ≤ Denote H(x) = Since H(x) ≥ 0 and 1 1 F (x)p + G(x)q − F (x)G(x) dµ = p q H(x)dµ = 0....e. Suppose f p = 0. Proof. |f (x)| dµ = 1.e.. and G(x) = |g| / g q . pk which implies that |f1 f2 . p q X then H(x) = 0 µ-a. then F 1 q G(x)q dµ. p then g We also ﬁnd f gdµ = f X 1−p p q q = f q−pq p |f (x)| X qp−q dµ = f p X |f (x)| dµ = f X p .e.Fn dµ ≤ X k=1 1 = 1. X p = G q = 1. but the equality holds only if F (x) = G(x)q µ-a. and f gdµ = f X p g q . g ≥ 0. Theorem 1. Assume in Holder’s inequality f ≥ 0. p q p for µ-a. Deﬁne F (x) = |f | / f We also ﬁnd by our assumption that F (x)G(x)dµ = 1 = X p. 2 . g q = 0. 1 p F (x)p dµ + X Since F. . fn pn . Prove that there exits g ∈ Lq with g q = 1 and f gdµ = f X p . Hence |f (x)| = This proves our assertion. Suppose f p . Theorem 1. X 1 1 F (x)p + G(x)q . for 1 ≤ k ≤ n. Proof.

Suppose 1 ≤ p < r < q < ∞.2. β ≤ 1 so that r = αp + βq. Suppose p. Prove that Lp ∩ Lq ⊂ Lr . Suppose f ∈ Lp ∩ Lq . |f g|r dµ ≤ X X (|f |r )p/r X r r r p r q (|g|r )q/r . then we can ﬁnd 0 ≤ α. α + β = 1. then f + g ∈ Lp and f +g Proof. Theorem 1.Proposition 1. Since |f + g|p ≤ 2p (|f |p + |g|p ) . ∞) and 1 1 1 = + . If 0 < a < ∞.1. we ﬁnd α β |f |r dµ ≤ X X |f |p dµ X |f |q dµ = f αp p f βq q < ∞. Proposition 1. It’s easy to see that by the Holder inequality. α β Then by the Holder inequality for 1/α. Assume 1 ≤ p < ∞ and assume f. 1/β. Then we ﬁnd fg which proves the inequality. Proof. Theorem 1. Since 1 < p < r < q. ≤ f p + g p . By the inequality of Holder. prove that |f |a This can be proved by the deﬁnition of p-norms. r ∈ [1. then we ﬁnd f + g ∈ Lp .6. f +g p p + g p . f +g p p p p = f a ap . we ﬁnd r/p r/q r ≤ f p g q . 3 . q. Therefore we see that f ∈ Lr .5. g ∈ Lp . Hence |f |r dµ = X X ≤ f g . = X |f + g|p dµ |f + g|p−1 |f + g|dµ X = ≤ X |f + g|p−1 |f |dµ + X 1/q |f + g|p−1 |g|dµ 1/q ≤ X |f + g|(p−1)q p−1 p f p+ p−1 p |f + g|(p−1)q X g p = f +g which implies that f p + f +g ≤ f g p . r p q Prove that fg Proof. |f |αp+βq dµ = X (|f |p ) (|f |q ) .